Analisis Rasio Profitabilitas dan Rasio Keuangan Sebagai Dasar Penilaian Kinerja Keuangan Pada PT. Indofarma (Persero) Tbk Periode Maret 2014-2018 - Fernawati, Amelia Fernawati (Nusa Putra University, 2020)
This study aims to determine the financial performance of PT Indofarma (Persero) Tbk in the period March 2014-2018 seen based on profitability ratios and activity ratios as well as performance appraisals based on Kasmir industry standards (2015). Using descriptive research methods. The object of research is the financial statements of PT Indofarma (Persero) Tbk. The type of data used in this study is secondary data. Data collection techniques in this research is to use the literature method. According to James C. Van Home in Kasmir (2015: 104) financial ratios are indices that connect two accounting numbers and are obtained by dividing one number by another. The results of this study indicate that the Company in terms of profit margins can be said to be healthy, because the Company's average profit margin of 31.5% is above the industry standard. Meanwhile, when viewed from the Company's net profit margin, return on investment, and return on equity it can be said to be unhealthy, because it is below the industry standard. While based on the activity ratio, the Company has not been able to manage its assets. This can be seen from the highest average working capital turnover of only 2.66 times which is below the industry standard. While the lowest average total assets turnover was 0.13 times which is below the industry standard. Then the Company's activity ratio is declared unhealthy. In addition, the Company's performance based on profitability ratios improved although it was still below the industry standard. Whereas according to the activity ratio the Company's performance has decreased and the calculation results are below the industry standard.